Природно-ресурсна сфера України: стан та шляхи збереження - Хвесик, М.А.; Обиход, Г.О. (Вісник НАН України, 2019)
За результатами проведених досліджень сучасного стану природно-ресурсної сфери, а також при визначенні пріоритетних напрямів і організаційно-економічних механізмів її збереження встановлено неоднорідність
розвитку регіонів за відповідними показниками, що потребує розроблення
спеціальних, а не уніфікованих підходів до нарощування соціально-економічного потенціалу окремих територій. Проведено оцінку ресурсного потенціалу природного багатства України за складовими земельних, лісових,
водних і мінеральних ресурсів та екосистемними послугами. Визначено рівень забезпеченості регіонів основними групами природних ресурсів, оцінено ступінь їх залучення до господарського використання. Обґрунтовано
пріоритетні напрями підвищення вартості наявних територіальних ресурсів і залучення їх у фінансовий обіг. Доведено необхідність організації відповідної системи управління, яка б забезпечувала, з одного боку, надання
природним ресурсам форми фінансових інструментів, а з іншого — гарантувала б їх ефективне проходження через адекватну фінансову інфраструктуру, що одночасно розширить можливості для активізації процесу їх відтворення. According to the results of the research conducted on the current state of the natural resource sphere, as well as in determining
the priorities and organizational and economic mechanisms for its preservation, the heterogeneity of regional
development is established according to relevant indicators. For the first time, using innovative methodology, the value
of the natural wealth of the country is determined. Indications and structure of the organizational, economic and institutional
mechanisms of the integrated economic assessment of the natural wealth of territories in the process of balancing
the natural resources use and effective management of sustainable development of the state are revealed. The use of
public-private partnership in the field of nature use is described, and the basic implementational principles of this model
have been represented at the regional and local levels. This requires the development of special, rather than unified, approaches
to building up the socio-economic potential of individual territories. In this context, an assessment of the resource
potential of the natural wealth of Ukraine is carried out. It includes land, forest, water and mineral resources, as
well as ecosystem services. The level of provision of regions with the main groups of natural resources is determined and
the degree of their economic use is assessed. The priority directions for increasing the value of available territorial resources,
their use in financial turnover are proposed and justified. The necessity of organizing an appropriate management
system, which would provide financial instruments for resource management and, on the other hand, would guarantee
their effective passage through an adequate financial infrastructure and at the same time expand the possibilities
for enhancing the process of their reproduction is shown.